Assessment of Men's Role on Mother Care when Pregnant, Birth and Breastfeeding - Mariana Ngundju Awang (Humanistic Network for Science and Technology (HNST), 2018)
Background: The maternal mortality rate (MMR) in East Sumba is one of the highest in the province of East Nusa Tenggara (NTT) for the past five years (2011-2015). Maternal mortality in East Sumba District is 76.7% occurred during childbirth and 23.3% during pregnancy. The Sumba tribe is based on patriaki culture which prioritizes men as the masters. Male participation is very small, but their control of women in deciding for women to use contraceptives or not very dominant. Methods: The type of research used was qualitative research by means of in-depth interviews and FGDs on 20 respondents. Results: Men were very instrumental in helping their wives from becoming pregnant, giving birth and breastfeeding according to cultural figures, customs, husbands and wives. Conclusion: The role of men when pregnant wives prepare themselves as prospective fathers by following the development of pregnancy and supporting the preparation of childbirth, when the wife gives birth to accompany the wife before and during childbirth by giving motivation to face the pain, struggle to give birth to the baby, and when breastfeeding wife Supports the success of breastfeeding, especially exclusive breastfeeding Keywords: Male role, East Sumba culture, Traditional figure, Religious figure